Design of a Dual-Band Sectoral Antenna for Hiperlan2 Application Using Double Layers of Metallic Electromagnetic Band Gap (M-EBG) Materials as a Superstrate - M. Hajj; R. Chantalat; B. Jecko (International Journal of Antennas and Propagation)
A novel design of a sectoral antenna that utilizes a double layer Metallic Electromagnetic Band Gap (M-EBG) as a superstrate for dual band directivity enhancement is presented in this paper. We obtain the different operating frequencies by adjusting the distance of the lower M-EBG layer from printed patch antenna and also the height between upper and lower M-EBG layers. This antenna operates according to a sectoral radiation pattern form presenting a half power beamwidth of at least 60∘. The proposed structure presents more than 17 dB directivity enhancement at 5.25 GHz and 5.65 GHz as compared to those of a patch antenna with 9 dB directivity. The principle is explained and applied to a Hiperlan2 antenna.